Assessing emotional aspects of midwives' intrapartum care: Development of the emotional availability and responsiveness in intrapartum care scale. (July 2019) - Leinweber, Julia; Creedy, Debra K.; Rowe, Heather; Gamble, Jenny
Abstract: Background/Problem: Emotional care underpins women's positive experiences during labour andbirth but is under-researched. Applying an attachment theory approach may inform the measurement of emotional aspects of maternity care. Objective: To develop and validate a self - report measure for midwives to assess their emotionally attuned intrapartum care. Methods: A staged approach to tool development was followed. Item generation was informed by a critical review of the literature and expert review. Following a pilot test, the draft scale was psychometrically assessed. Principal component analysis with varimax rotation was used to establish construct validity. Cronbach's alpha determined internal reliability. Concurrent validity was tested with the 'empathic concern' and the 'personal distress' subscales on the Interpersonal Reactivity Index. The study was conducted with midwives (n = 705) who are members of the Australian College of Midwives. Findings: The Cronbach's alpha for the scale was 0.88. Principal component analysis revealed a one- factor solution. Significant but low correlations with Interpersonal Reactivity Index subscales of 'empathic concern' (rho = .256, p <.001) and 'personal distress' (rho = −.249, p<.001) confirmed concurrent validity. Conclusion: The Emotional Availability and Responsiveness in Intrapartum Care Scale appears to be a valid and reliable measure of emotional aspects of midwives' caregiving. An Attachment Theory approach validates women's perspectives and elucidates our understanding of the importance of emotional labour support.